Pengaruh Persepsi Mahasiswa tentang Pendidikan Berbasis Nilai terhadap Sensitivitas Sosial - Asmaul Husnah Amiruddin; Hasni Hasni; Nurazizah Rahmi; Sagita Ramadhana; Ulul Azmi Mustari (Universitas Methodist Indonesia, 2026)
This study aims to analyze the perceptions of students in the Social Studies Education Study Program at Makassar State University toward value-based learning, the level of students’ social sensitivity, and the relationship between these two variables. This research employed a quantitative approach with a correlational design. Data were collected through a closed-ended questionnaire distributed to 165 Social Studies Education students at Universitas Negeri Makassar and were analyzed using descriptive and inferential statistical techniques assisted by IBM SPSS. The results indicate that students’ perceptions of value-based learning fall within the moderate to high category, with a predominance of the moderate category, suggesting that value-based learning has been implemented and reasonably well received, although not yet optimal. Students’ social sensitivity is in the moderate category, particularly in the indicators of critical awareness, social concern, and sensitivity to the social environment. Furthermore, the analysis reveals a very strong and significant relationship between students’ perceptions of value-based learning and their social sensitivity. These findings conclude that value-based learning plays a strategic role in enhancing students’ social sensitivity; therefore, it needs to be developed in a more integrated, reflective, and contextual manner in Social Studies learning at the higher education level.